KESESUAIAN HASIL PEMERIKSAAN ULTRASONOGRAFI DAN HISTOPATOLOGI PADA PASIEN TUMOR PAYUDARA DI RSUD ARIFIN ACHMAD PERIODE 1 OKTOBER 2013 - 30 SEPTEMBER 2014 - Indira Suluh Paramita; Andreas Makmur; Effif Syofra Tripriadi (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACT This study aims to know the concordance of ultrasonography and histopathology results in diagnosing breast tumor at Arifin Achmad General Hospital. This study was an analytic retrospective with a cross-sectional design. Samples in this study includes all breast tumor patients that went through ultrasonography and histopathology examinations during 1 october 2013 – 30 september 2014. There were 31 samples that fulfilled the inclusion criteria. All samples were females. This study shows that breast tumor is most frequent in age group 40-49 years old with 15 patients (4,39%). Among 15 patients, 10 were diagnosed with benign tumor (32,26%) and 5 were diagnosed with malignant tumor (16,13%). Kappa scores of ultrasonography and histopatology was R 0,353, it means the concordance was fair. Overall, ultrasonography concordance accuracy was 70,96%. Concordance in diagnosing benign tumor was 80% and was 54,5% in malignant tumor.Keywords : Breast tumor, ultrasonography examinations result, histopatology examinations result.